2019
DOI: 10.1021/acs.iecr.9b04881
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Gas Permeability and Young’s Modulus during the Physical Aging of Polymers of Intrinsic Microporosity Using Atomic Force Microscopy

Abstract: The relationship, during physical aging, between the transport properties and Young's modulus for films of polymers of intrinsic microporosity (PIM) was investigated using pure gas permeability and atomic force microscopy (AFM) in force spectroscopy mode. Excellent agreement of Young's modulus measured for the archetypal PIM-1 with values obtained by other techniques in the literature, confirms the suitability of AFM force spectroscopy for the rapid and convenient assessment of mechanical properties. Results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 60 publications
2
13
2
Order By: Relevance
“…However, the conceived adsorbent may display mechanical weakness and tend to excessively swell/plasticize, which is prohibitive for practical adsorption applications. This can be further placed in connection with recent work by Longo et al 64 that observed correlated behavior between Young's modulus and the mass transport properties of six different tested PIMs. In this context, it is understood that various adsorbent material properties can be interconnected and as a result provide additional levels of complexity to the adsorbent design process.…”
Section: Resultssupporting
confidence: 72%
“…However, the conceived adsorbent may display mechanical weakness and tend to excessively swell/plasticize, which is prohibitive for practical adsorption applications. This can be further placed in connection with recent work by Longo et al 64 that observed correlated behavior between Young's modulus and the mass transport properties of six different tested PIMs. In this context, it is understood that various adsorbent material properties can be interconnected and as a result provide additional levels of complexity to the adsorbent design process.…”
Section: Resultssupporting
confidence: 72%
“…Indeed, volume shrinkage could be detrimental for the glass lifetime [ 9 ]; therefore, aging must be by glass manufacturers to avoid any undesired alteration of properties over the course of time. Notable examples in this sense are those on the effect of aging on gas transport properties [ 10 , 11 , 12 , 13 ] also in relation to mechanical properties [ 14 ]. The relation between gas transport properties and the thermodynamic state of the glass has also been discussed [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, the data measured under the same conditions by Longo et al for PIM‐1 after MeOH treatment (○) and 2219 days of ageing (◆) are indicated in green. [ 22 ] Other literature data are reported in grey symbols for PIM‐1 (+), SBF‐based PIMs (O), ultrapermeable triptycene based PIMs () and PTMSP (×).…”
Section: Resultsmentioning
confidence: 99%